The Effect of Workload and Compensation System on Turnover Intention with Job Satisfaction as a Mediating Variable in PT. Xyz - Vindi Putri Kurnia Illahi; Rahmi Fahmy; Laura Syahrul (International Journal Labs, 2022)
Background: The problem of limited Human Resources (HR) and competition is a major obstacle to the growth of the industry, especially in the banking industry. This problem then also causes other problems such as the high employee turnover rate which has now become a separate problem for many companies. The high employee turnover rate experienced by a company can be predicted by how much desire to move company members have to other companies. PT. XYZ is one of the Islamic banking companies that has experienced an increase in the turnover rate of its employees from year to year. Objective: This study aims to examine and build a conceptual model of the effect of workload and compensation systems on the turnover intention with job satisfaction as a mediating variable in PT. XYZ. Method: This study used a non-probability sampling technique with the sample used being 70 permanent employees through the distribution of questionnaires. Results: This study found that job satisfaction does not mediate the effect of workload on turnover intention, but job satisfaction can mediate the variable of the compensation system against turnover intention in PT. XYZ. Conclusion: PT. XYZ has not been able to provide a workload that is by the abilities of its employees, coupled with compensation that is not by the workload that is fished so as to reduce the level of employee work loss which ultimately increases the intensity of employee turnover intention at PT. XYZ.